Analisis Pengaruh Revitalisasi Toko Merah Kota Tua Jakarta Terhadap Preferensi Berkunjung Wisatawan - Febrian, Andrew; Iskandar, Hari (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This study aims to analyze the impact of the revitalization of Toko Merah in Kota Tua Jakarta on tourists' visiting preferences. The revitalization efforts included improvements and enhancements to attractions, amenities, accessibility, and services at Toko Merah. The research method used is quantitative, with data collection through questionnaires distributed to 400 respondents who have or have not visited Toko Merah. The results indicate that the revitalization of Toko Merah significantly affects tourists' visiting preferences. Most respondents (98.3%) who have visited expressed a high interest in the destination after the revitalization. Data analysis also shows that the dimensions of attractions, amenities, accessibility, and services each positively contribute to increasing tourists' interest in visiting. The conclusion of this study is that the revitalization of Toko Merah in Kota Tua Jakarta successfully enhances tourists' visiting preferences. This can serve as a reference for stakeholders in planning and executing the revitalization of other heritage buildings to increase tourist attraction. Recommendations include increasing promotions to reach segments of the community who have not yet visited and adjusting tourism services according to tourists' preferences and expectations.